Microphysics of the aqueous bulk counters the water activity driven rate acceleration of bromide oxidation by ozone from 289–245 K. Issue 1 (10th December 2018) - Edebeli, Jacinta; Ammann, Markus; Bartels-Rausch, Thorsten
Abstract : Microphysics of the aqueous bulk counters rate acceleration of bromide oxidation by ozone at low temperatures. Abstract : The reaction of ozone with bromide is an initiation process in bromine activation resulting in the formation of reactive bromine species with impacts on the fate of compounds in the lower atmosphere. Environmental halide sources often contain organics, which are known to influence aqueous bulk reactivity. Here, we present a study investigating the temperature dependence of bromide oxidation by ozone using a coated wall flow tube reactor coated with an aqueous mixture of citric acid, as a proxy for oxidized secondary organic matter, and sodium bromide. Using the resistor model formulation, we quantify changes in the properties of the aqueous bulk relevant for the observed reactivity. The reactive uptake coefficient decreased from 2 × 10 −6 at 289 K to 0.5 × 10 −6 at 245 K. Our analysis indicates that the humidity-driven increase in concentration with a corresponding increase in the pseudo -first order reaction rate was countered by the colligative change in ozone solubility and the effect of the organic fraction via increased viscosity and decreased diffusivity of ozone as the temperature decreased. From our parameterization, we provide an extension of the temperature dependence of the reaction rate coefficients driving the oxidation of bromide, and assess the temperature-dependent salting effects of citric acid on ozone solubility. This study shows the effects of the organic species at relatively mild temperatures, between the freezing point and eutectic temperature of sea as is typical for the Earth's cryosphere. Thus, this study may be relevant for atmospheric models at different scales describing halogen activation in the marine boundary layer or free troposphere including matrices such as sea-spray aerosol and brine in sea ice, snow, and around mid-latitude salt lakes.